Process optimization of vacuum fried eggplant (Solanum melongena L.var. fortuner F1) chips using response surface methodology - Baoas, Emmanuel Nathan D. (College of Home Economics, University of the Philippines Diliman, 2018)
This study aimed to optimize the process for vacuum fried eggplant (Solanum melongena L. var. Fortuner F1) chips using response surface methodology. Specifically, the study (1) evaluated the effects of time and temperature on the quality of vacuum frying of eggplant chips using central composite design response surface methodology; (2) established and verified the optimum process parameters for the vacuum frying process of eggplant chips; and, (3) established the product profile (physico-chemical, proximate, microbiological and consumer acceptability) of vacuum fried eggplant chips. Vacuum frying process parameters temperature generally had a significant (p<0.05) effect on product yield, color L*, water activity (Aw), appearance acceptability, and texture (crispness) acceptability. The optimum process parameter for vacuum fried eggplant chips was at 92.25°C for 5.09-9.64 min having a desirability score of 0.725. Models can accurately predict the values for responses based on verification studies. In general, the optimized sample passed the microbiological standards for fried snack food (≤104 cfu/g APC, ≤102 cfu/g YMC, and <10 MPN/g coliform count) and is a good source of carbohydrates, fat, and fiber. The findings in this study showed that the parameters mentioned should be used to produce the best quality vacuum fried eggplant chips using the DOST-HITS fabricated vacuum fryer under constant pressure of 6 KPa. The product has a potential as a healthier alternative fried snack.